Public Service Motivation: Can Remuneration Increase Job Satisfaction and Performance in Organization Sector Public? - Priyastiwi Priyastiwi; Sofiati Sofiati (Trunojoyo University of Madura, 2022)
This study examines the effect of public service motivation and remuneration on job satisfaction and employee performance. The study also examines whether remuneration will moderate the relationship between public service motivation with job satisfaction and performance based on crowding out the theory. This study investigates whether extrinsic motivation in remuneration will reduce intrinsic motivation (public service motivation). Data collection and sampling: The data for this research was collected from primary sources. Data was collected by distributing the questionnaires to the employee in Office Tax in Daerah Istimewa Yogyakarta. The study has used the partial least square (PLS) approach to analyze the data. The study has used PLS due to its ability to examine the causal relationship between the variables. At the same time, it deals with the constructs and measurement items, thus making it a feasible option to use. Research results prove that public service motivation and remuneration positively influences work satisfaction and performance. Public service motivation and remuneration influences performance mediated satisfaction. Payment does not moderate relationship motivation to satisfaction because that p-value has lower than the required. Remuneration policy weakens influence public service motivation to dignity. However, the path coefficient is worth negative. So with a policy, applicable remuneration now precisely cut influence job satisfaction, which could lower performance. Theory crowding-out show that gift remuneration as award extrinsic to increase job satisfaction and performance of employees government.